Evaluation of pollution level caused by domestic effluent in the Poty river – Teresina PI - Brazil - Damasceno, Izabele Folha; Leal, Vivane Lopes; Coelho, Ronaldo Cunha; de Moura, Carla Verônica Rodoarte; de Moura, Edmilson Miranda (Eclética Química, 2014)
This article reports on the level of contamination of effluents, sediments and water in the Poty River, within the city of Teresina. The samples were collected in the months of September 2009, December 2009 and March 2010. The results of some physico-chemical parameters investigated, as well as the concentrations of lead, copper and nickel found in the river water samples showed that the body of water in the Poty River is unsuitable for use in various activities. These activities include direct recreational usage and primary irrigation of vegetables that are eaten raw as well as fruits that are eaten without removing films, among others.